Implementation of the Dengue Fever Prevention Program at the Tanah Tinggi Primary Health Care in Binjai - Annisa Aisy Rifdah; Hasibuan, Rapotan (Universitas Nahdlatul Ulama Surabaya, 2024)
Dengue hemorrhagic fever is one of the public health problems in Indonesia that is currently increasing the number of patients and its spread is increasingly widespread. In Binjai, the Primary Health Care (PHC) classified as the highest DHF case is the Tanah Tinggi Primary Health care (TTPHC) from 2020 there were 4 cases, 2021 34 cases and 2022 102 cases. This study aims to investigate the implementation of the DHF prevention program. This research used Qualitative methods with a case study research design. Data obtained from in-depth interviews with 6 (six) informants. The research was conducted at TTPHC in Binjai from February to May 2023. The results showed that inputs including human resources were sufficient, facilities and infrastructure were incomplete, and funds came from the health operational assistance (BOK). There were still processes of P2DBD program activities which not carried out optimally, namely fogging. There were still some outputs/achievements of each P2DBD program activity that had not reach the target, namely fogging. Keywords: Dengue, implementation, program, P2DBD, tanah tinggi